Barriers and strategies in detection and management of elevated Lipoprotein(a) in hospital: A pre-implementation qualitative study of cardiology healthcare professionals - Wann-Jia Loh; Linh Thai; Bik-Ling Poon; Jonathan Yeo; Jian-Jing Tan; Elaine Lum (PLoS ONE, 2025)
Background Elevated Lipoprotein(a) [Lp(a)] is a genetic risk factor for cardiovascular diseases affecting 20% of the world’s population, with multiple published consensus statements that recommend testing and management strategies. However, elevated Lp(a) remains under-detected and under-treated worldwide. Our qualitative study explored the perspectives of cardiology healthcare professionals regarding the barriers and enablers for Lp(a) detection and management. Methods Guided by Theoretical Domains Framework, we conducted 41 qualitative semi-structured one-on-one interviews in a cardiology department at a high-volume hospital in Singapore from October to December 2023. Healthcare professionals were purposively sampled across role and seniority to include doctors (specialists and interns), specialist nurses and dedicated pharmacists. Through an inductive process, we constructed qualitative codes followed by code-mapping to arrive at higher-order sub-categories, categories, and eventually themes. Results Analysis revealed 4 themes: rationale for routine testing, barriers to testing and follow-up, enablers of testing and follow-up, and ideal system to enhance patient management. Critical barriers to Lp(a) testing included a perceived lack of guidance in testing and follow-up, and misperception that Lp(a)-mediated cardiovascular risk cannot be managed resulting in low confidence of healthcare professionals to detect and manage elevated Lp(a). Inadequate institutional support to alleviate workload and presumed patient aversion to testing further hindered Lp(a) testing. We identified enablers and strategies to testing and management of Lp(a), notably these were the need for hospital-wide adequate training and education, guidelines and risk management pathways applicable to local settings, integration of Lp(a) testing into existing clinical pathways for high-risk patients, and user-friendly decision aids for healthcare professionals. Conclusion Effective education for healthcare professionals and optimised clinical workflows may help to address current knowledge gap and implementation barriers in the detection and management of elevated Lp(a) in hospital.